Pengaruh Penggunaan Metode Mind Mapping Terhadap Hasil Belajar Tematik Siswa Kelas V SD Kota Bengkulu - Bella Anissah; Sri Dadi (Universitas Bengkulu, 2023)
This study aims to analyze the effect of the use of mind mapping methods on the thematic learning outcomes. This is quantitative research. The method used was quasy experimental with the type of research design The Matching Only Pretest-Posttest Control Group Design. The population is the fifth grade students of the XIX cluster in Bengkulu City. The sampling uses the Cluster Random Sampling technique. The sample in this study was the VA class SDN 69 Bengkulu City, totaling 28 students as the experimental class and VB SDN 72 Bengkulu City totaling 22 students as the control class. The research instrument used test Pretest and Posttest, for the attitudes and skills learning outcomes of the instrument used was an observation sheet. Data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics. From the results of the study note the results of the t-test obtained tcount of Indonesian subjects of 2.47, social studies subjects of 2.51, and Civics subjects of 3.11 with a table at a 2.01 where tcount is greater from ttable. Thus it can be concluded that there is a significant influence on student learning outcomes in Thematic learning using mind mapping methods.